Penggunaan Metode Systematic Literatur Review Untuk Menganalisis Artikel Sistem Pakar Metode Forward Chaining - Resnawita; Billy Hendrik (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2023)
The development of AI or artificial intelligence has entered the forefront of the world of technology. Artificial intelligence can be one solution to various problems. One algorithm that uses an AI program is an expert system algorithm where the expert system is an AI program with a knowledge base (Knowledge Base) obtained from experience or expert knowledge or experts in solving problems in certain fields. The forward chaining method is one method of system development, which is a method with decision making that begins with considering information or facts before drawing final conclusions. With the use of the forward chaining method, the system is designed to operate on various devices such as web, mobile, or desktop. This study uses a systematics literature review (SLR) methodology, aims to determine the fields, platforms, and advantages and disadvantages of using the forward chaining method for expert systems that rely on information from related journals between 2020 and 2023